Penerapan Green Housekeeping untuk Meningkatkan Efisiensi Biaya Operasional pada Housekeeping Department Holiday Resort Lombok - I Ketut Murta Jaya Kusuma; Dewa Made Suria Antara; Ni Gst Nym. Suci Murni; Raden Roro Rieta Anggraheni (Jurnal Manajemen Perhotelan dan Pariwisata, 2023)
This observation-based research aims to investigate the impact of the implementation of green housekeeping at the Holiday Resort Lombok, particularly on the operational cost efficiency. The data were collected in three months through observation, interview, and documentation technique, involving as many as 4 (four) informants. The data were analyzed using descriptive quantitative analysis technique and the discussion was focused on the influence of Internal and External factors on the efficiency of operational cost. The research result shows that the implementation of green housekeeping has a positive impact in decreasing the operational cost and increasing the amount of savings yearly. In 2018, before the implementation of green housekeeping, the total savings of operational cost was Rp 2.045.750.506, while in 2019 there was a greater amount, indicating a significant result by 18.43% more frugal due to the green housekeeping implementation. Studying the global trend of green hotel, Holiday Resort wants to point out and emphasize the advantages offered by the green hotels. This also suggests that Holiday Resort can become a more competitive destination considering its potential and resources. However, it is recommended that Holiday Resorts Lombok allocate more funds for composting and vermi composting, biomethanation, and biosanitizing processes.